2005
DOI: 10.1111/j.1398-9995.2005.00824.x
|View full text |Cite
|
Sign up to set email alerts
|

Dog factor differences in Can f 1 allergen production

Abstract: Breeds (Labrador retriever), sex and seborrhea seem to influence the levels of Can f 1 on fur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
30
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 15 publications
(14 reference statements)
2
30
1
Order By: Relevance
“…There may be several possible reasons for the observed heterogeneities of the extracts: (i) different starting material from which manufacturers extract allergens (hair, dander or/and epithelium) may contain different allergens [8,26], (ii) the levels of the major dog allergen Can f 1 may vary between dog breed and sex and between individual dogs of the same breed [27], (iii) different extraction techniques as well as the presence of stabilizers like glycerol and phenol might contribute to differences in extract composition [14,28]. …”
Section: Discussionmentioning
confidence: 99%
“…There may be several possible reasons for the observed heterogeneities of the extracts: (i) different starting material from which manufacturers extract allergens (hair, dander or/and epithelium) may contain different allergens [8,26], (ii) the levels of the major dog allergen Can f 1 may vary between dog breed and sex and between individual dogs of the same breed [27], (iii) different extraction techniques as well as the presence of stabilizers like glycerol and phenol might contribute to differences in extract composition [14,28]. …”
Section: Discussionmentioning
confidence: 99%
“…4,6 Breed-specific allergens have not been identified. 4,6,7 Only 2 studies 6,8 have explored differences between levels of Can f 1, a major dog allergen (Canis familiaris), 4,9 in hair from different dog breeds.…”
mentioning
confidence: 99%
“…However, this unequal distribution on fur could result from licking and grooming which is specific for cats. In contrast, Can f 1 concentrations have been found to be similar between different anatomical zones of dogs [16] . According to Kurosumi et al [25] , nonprimate mammals have apocrine sweat glands (producers of Bos d 2 in cattle) over the greater part of their body.…”
Section: Discussionmentioning
confidence: 81%
“…Ramadour et al [16] reported that male dogs had significantly higher Can f 1 concentrations in their hair compared to female dogs, although the difference was small (11.75 vs. 8.89 μg/g, p = 0.037) [16] . No significant effect of sex on Can f 1 levels was seen in the study by Vredegoor et al [15] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation